Preferences, power and policy outcomes in public policy in Iceland: The Icelandic Housing Fund fiasco 2003-2005 - Sigurbjörg Sigurgeirsdóttir (Veftímaritið Stjórnmál og stjórnsýsla, 2014)
This research focuses on the interplay of politics, bureaucracies and markets in Iceland. It aims to explain theoretically how politics and bureaucracies operate when a coalition government makes and implements decisions in a policy environment in which decisions and their effects intersect public bureaucracies’ and markets’ boundaries. The decision to raise the limits of Housing Fund mortgages in 2003 is a case examined by agenda-setting theories in public policy. The research is based on the data from parliamentary Special Investigation reports on the collapse of the Icelandic banks and the Housing Fund as well as the author’s interviews home and abroad. The research shows that, when made, the decision ignited competition between the Housing Fund and the recently privatized banks and that between the banks themselves. The Independence Party’s attempts to delay implementation of the decision involved system change backed by an instrument designed to stem a run on the Fund. The impact of this instrument (a tax on pre-payments) was incompatible with the Progressive Party’s political interests. In a hasty attempt to implement its election promises, the Progressive Party ignored the fact that the Fund was operating within a transformed financial system. The conclusions indicate that those who think long-term in politics make policies by changing system dynamics, those who think short-term change programmes. System dynamics, however, change the balance of power and influence between actors, leaving legacies which curb the government’s attempt at change, unless consolidated and sustained political authority and will are established to see changes through.